THE ANTIOXIDANT ACTIVITY AND PHYTOCHEMICAL SCREENING OF ETHANOL EXTRACT, FRACTIONS OF WATER, ETHYL ACETATE AND n-HEXANE FROM MISTLETOE TEA (SCURRULA ATROPURPUREABL. DANS) - Mustarichie, Resmi; DUDI RUNADI; DANNI RAMDHANI (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The aim of this study is to investigate antioxidant activity and phytochemical screening of ethanol extract, fractions of water, ethyl acetate, and n-hexane from mistletoe tea (Scurrula atropurpurea Bl. Dans). Methods: Simplicia extracted using soxhlet equipment with 96% ethanol. Fractionation was conducted using liquid-liquid extraction using a solvent of water, ethyl acetate and n-hexane. Screening of phytochemical and antioxidant activity was performed against these fractions. Antioxidant activity was determined by 2,2-diphenyl-1-picrylhydrazyl method using ultraviolet-visible spectrophotometry with ascorbic acid as standard. Phytochemical screening was conducted based on the method of Farnsworth. Results: The IC50 values of ethanol extract, water fraction, fraction of ethyl acetate, and n-hexane fraction were 21.92 ppm, 89.57 ppm, 14.08 ppm, and 162.09 ppm, respectively, whereas for ascorbic acid was 4.41 ppm. The ethanol extract and ethyl acetate fraction contained compounds were the same group, polyphenolic, tannins, flavonoids, monoterpenoid, steroids, triterpenoids, and quinones. Fraction of water contained compounds such as polyphenolic group, flavonoids, monoterpenoids, sesquiterpenoids, steroids, and triterpenoids. n-hexane fraction compounds contained steroids and triterpenoids. Conclusion: The ethanol extract, water fraction, ethyl acetate fraction, and n-hexane fraction showed antioxidant activities. The ethanol extract, fractions of water, and ethyl acetate fraction contained flavonoids and polyphenolic potential as antioxidants. Keywords: Mistletoe tea, Scurrula atropurpurea, Antioxidant, 2,2-diphenyl-1-picrylhydrazyl, Ascorbic acid.